Synthesis and Thermoelectric Properties in the 2D Ti(1 – x)Nb(x)S(3) Trichalcogenides - Misse, Patrick R. N. (Materials (Basel), 2015)
A solid solution of Ti(1 − x)Nb(x)S(3) composition (x = 0, 0.05, 0.07, 0.10) was synthesized by solid-liquid-vapor reaction followed by spark plasma sintering. The obtained compounds crystallize in the monoclinic ZrSe(3) structure type. For the x = 0.07 sample, a mixture of both A and B variants of the MX(3) structure is evidenced by transmission electron microscopy. This result contrasts with those of pristine TiS(3), prepared within the same conditions, which crystallizes as a large majority of A variant. Thermoelectric properties were investigated in the temperature range 323 to 523 K. A decrease in the electrical resistivity and absolute value of the Seebeck coefficient is observed when increasing x due to electron doping. The lattice component of the thermal conductivity is effectively reduced by the Nb for Ti substitution through a mass fluctuation effect and/or a disorder effect created by the mixture of both A and B variants. Due to the low carrier concentration and the semiconductor character of the doped compounds, the too low power factor values leads to ZT values that remain smaller by a factor of 50 than those of the TiS(2) layered compound.